+0  
 
0
172
3
avatar

 Which of the following is equivalent to the expression (9x^2y^3) (12x^-3y^5) (2xy)

A: 23x^-5y8
B: 216y^9
C: -x^-6y^8

D: -216x^-7y^15

 

 A little math question I had for homework I couldn't solve. Any help?

Guest Apr 27, 2017
Sort: 

3+0 Answers

 #1
avatar+26366 
+1

(9x^2y^3) (12x^-3y^5) (2xy) → (9*12*2)*(x^2*x^-3*x)*(y^3*y^5*y) → 216*(x^[2-3+1])*(y^[3+5+1]) → 216*x^0*y^9 → 216*y^9

.

Alan  Apr 27, 2017
 #2
avatar+91259 
+2

(9x^2y^3) (12x^-3y^5) (2xy)

 

\((9x^2y^3) (12x^{-3}y^5)(2xy)\\ =9x^2y^3* 12x^{-3}y^5*2xy\\ =9*12*2\;x^2 x^{-3}x^1y^3y^5y^1\\ =216\;x^{2+-3+1}y^{3+5+1}\\ =216\;x^{0}y^{9}\\ =216\;y^{9}\\ \)

Melody  Apr 27, 2017
 #3
avatar
0

Opuść nawiasy i zredukuj wyrazy podobne 

 

a) 3(a-5)+4(7+a)
b) 1,5(ab+2)-6(ab-1)
c) -(2x²-y+xy)+2(x²-3y-xy)
d) -3(0,5xy+2x)-5(-3xy-x)

Guest Apr 27, 2017

11 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details